State of the Kansas swine industry - Moore, B.L.; Schroeder, Ted C.; Langemeier, Michael R.; Flinchbaugh, Barry L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The Kansas hog industry represented 3.8% of U.S. hog production in 1977 and had peak production of nearly 3.4 million head in 1971. Since that time, the industry has declined significantly, representing only 2.5% of U.S. hog production with 2.5 million head produced in 1992. Kansas hog production has declined, while neighboring Nebraska has enjoyed increased production and share of U.S. production. Kansas hog production is also highly concentrated, with the largest 3.5% of producers owning 45.5% of the state's hog inventory. Efforts to identify specific causes and to change the economic environment will be required to reverse the decline in the Kansas swine industry.
Keywords: Swine; Swine industry trends; Hog marketings; Swine industry structure